CONSUMER SENTIMENT OF RURAL POPULATION: ANALYSIS OF SOCIAL FACTORS - Македон, Г. М. (Scientific Progress & Innovations, 2015)
The focus of attention is on the impact of the population’s behavior on the state's economy. Method of calculating the Index of Consumer Sentiment (ICS) was researched. ICS dynamics of rural population in Ukraine over the last year was analyzed. Rural households are less sensitive to political changes and escalating conflict in eastern Ukraine because their ICS is higher than in urban citizens. National indicators is compared with similar in foreign countries. We established that consumer confidence is the highest in Asia. We recommended to learn the experience of these countries to increase consumer sentiment of population in Ukraine.